Pengaruh Kebijakan Dividen Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Yang TerdaftarDi Bursa Efek Indonesia Tahun 2012-2014 - Andriyani, Andriyani; , Dra. W.Mukharomah, MM (2017)
This research aimed to analyze the influence of dividend policy on firm value in companies listed on Indonesian Stock Exchange (BEI) in the period 2012to 2014. Variables used in this research is Dividend Payout Ratio (DPR), Earning Per Share (EPS) and Firm Size. The research sample consisted of 22 companiesof 143 in a manufacturing companies listed on BEI. by the observation numbersof 66 observational data. The sampling method was done by using purposivesampling. The researched data was obtained from ICMD and IDX. The data analysis technique used in this research is multiple linear regression. Hypothesistesting using t statistics used in this research to test the partial regressioncoefficients as well as f-statistics to test the significance of the influence together,with the level of significance of 5%. Other than that, all the variables had beentested with the Normality test, Multicollinearity test, Autocorrelation test,andHeteroskidastity test. The results showed that all variables passed the classicalassumption test and suitable to be used as research data. T-test statisticalindicated that Dividend Payout Ratio (DPR), Earning Per Share (EPS) hassignificant influence on corporate (PBV), however variable firm size does notsignificant influence on corporate (PBV).